2017
DOI: 10.1016/j.neuron.2017.06.036
|View full text |Cite
|
Sign up to set email alerts
|

On the Integration of Space, Time, and Memory

Abstract: The hippocampus is famous for mapping locations in spatially organized environments and several recent studies have shown that hippocampal networks also map moments in temporally organized experiences. Here I consider how space and time are integrated in the representation of memories. The brain pathways for spatial and temporal cognition involve overlapping and interacting systems that converge on the hippocampal region. There is evidence that spatial and temporal aspects of memory are processed somewhat diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
361
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 429 publications
(374 citation statements)
references
References 120 publications
(157 reference statements)
8
361
0
5
Order By: Relevance
“…The results revealed that both of these variables independently contributed to the firing of most CA1 units, suggesting that the hippocampus encodes both spatial and temporal information. This finding suggests that hippocampal ensembles carry a multiplexed representation that could be used to localize an event in time, space, or both (Eichenbaum, ). The findings of time cells in rodents appear to generalize to primates.…”
Section: Hippocampal Encoding Of Continuous Temporal Intervalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results revealed that both of these variables independently contributed to the firing of most CA1 units, suggesting that the hippocampus encodes both spatial and temporal information. This finding suggests that hippocampal ensembles carry a multiplexed representation that could be used to localize an event in time, space, or both (Eichenbaum, ). The findings of time cells in rodents appear to generalize to primates.…”
Section: Hippocampal Encoding Of Continuous Temporal Intervalsmentioning
confidence: 99%
“…Mankin and colleagues (Mankin et al, ; Mankin, Diehl, Sparks, Leutgeb, & Leutgeb, ) extended these findings by demonstrating that the ensemble code for spatial location in CA1 drifts considerably across successive days (see also Rubin, Geva, Sheintuch, & Ziv, , for similar findings; Ziv et al, ), and in area CA2, population codes changed considerably over the course of hours. These findings suggest that temporal context might be an important mechanism by which the hippocampus may support episodic memory (Eichenbaum, ; Ekstrom & Ranganath, ; Ranganath & Hsieh, ). For example, temporal drift in hippocampal coding could allow the hippocampus to assign different representations to successive events that occurred in the same spatial context (e.g., last night's dinner party vs. last month's dinner party).…”
Section: Hippocampal Encoding Of Continuous Temporal Intervalsmentioning
confidence: 99%
“…To specify, episodic memory involves (a) single episodes encompassing longer periods of time (seconds to minutes and longer) (Ferbinteanu, Kennedy, & Shapiro, ; Shapiro, Kennedy, & Ferbinteanu, ; Smith & Mizumori, ), (b) knowledge of temporal relationships across episodes, and (c) retrieval of episodes long after initial storage. Although recent work has provided promising clues (Attardo, Fitzgerald, & Schnitzer, ; Cai et al, ; Driscoll, Pettit, Minderer, Chettih, & Harvey, ; Eichenbaum, ; Eichenbaum, ; Eichenbaum, ; Ezzyat & Davachi, ; Ferbinteanu & Shapiro, ; Frank, Stanley, & Brown, ; Hsieh, Gruber, Jenkins, & Ranganath, ; Karlsson & Frank, ; Kitamura et al, ; Ludvig, ; Mankin et al, ; Mankin et al, ; Manning, Polyn, Baltuch, Litt, & Kahana, ; Manns, Howard, & Eichenbaum, ; Murray et al, ; Ranganath & Hsieh, ; Rubin, Geva, Sheintuch, & Ziv, ; Runyan, Piasini, Panzeri, & Harvey, ; Suh, Rivest, Nakashiba, Tominaga, & Tonegawa, ; Ziv et al, ), the neural representation of events at longer timescales remains unclear. More knowledge and insight are needed.…”
Section: Three Brain States In the Hippocampusmentioning
confidence: 99%
“…The hippocampus has a critical role in binding incoming information (including semantic and episodic information and without regard to conscious awareness of the incoming information) into lasting relational representations. The information that is bound by the hippocampus is received from broader MTL structures . The perirhinal cortex (PRC), entorhinal cortex (ERC), and parahippocampal cortex (PHC)—brain regions located within the MTL—support representations of items composed of complex combinations of features, the configural arrangement of features within and among items, and the broader spatial and nonspatial context of the surrounding environment, respectively.…”
Section: The Role Of the Hippocampus And The Extended Mtl System In Mmentioning
confidence: 99%